Computational micromechanics model for the analysis of fiber kinking in unidirectional fiber-reinforced polymers. (March 2020) - Herráez, M.; Bergan, A.C.; Lopes, C.S.; González, C.
Highlights: Development of a novel experimental technique to characterize the compressive strength of reinforcement fibers. Development of a simplified micromechanical model to homogenize the nonlinear shear curve of a unidirectional composite lamina. Validation of an efficient numerical model to analyze fiber kinking initiation (compressive strength) and damage evolution during kink band broadening. Qualitative and quantitative assessment of the post-peak features typical of fiber kinking: kink band broadening, residual crushing stress and fiber rotation. Evaluation of the influence of the fiber-matrix interface strength and friction on the initiation and evolution of fiber kinking. Abstract: A computational micromechanics (CMM) model is developed to analyze fiber kinking, which is a failure mechanism that takes place in fiber-reinforced composites when they are loaded under longitudinal compression. The CMM model consists of a single AS4 carbon fiber with an initial misalignment embedded in an 8552 polymer matrix. The deformation of the model is governed by periodic boundary conditions (PBC). The relatively simple CMM model enables the evaluation of the role played by initial misalignment of the fiber, shear yielding of the matrix and fiber-matrix debonding. A novel microscale experimental technique devoted to the characterization of the longitudinal compressive strength of the fibers, X c f, is developed. By exercising the model and comparing it with several models in the literature, the nonlinear shear response of the composite lamina is shown to play a fundamental role not only in the prediction of the compressive strength Xc, but also during the post-peak regime in terms of residual stress σr and fiber rotation φ. Finally, the influence of the fiber-matrix interface damage (not considered in most other fiber kinking models) on the fiber kinking phenomenon is assessed through a parametric study.